2020
DOI: 10.1097/bsd.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Direction and Severity of Root Compression Affects the Clinical Outcome After Decompression?

Abstract: Study Design: This was a retrospective cohort study. Objective: To evaluate the correlation between preoperative radiologic degree and the postoperative prognosis in lumbar foraminal stenosis (LFS) patients who required decompression. Summary of Background Data: There have been only a few studies for postoperative prognosis according to the degree of preoperative stenosis in patients requiring surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, the results in our study don't seem to support this tendency Table 7 .This is in line with the North American Spine Society (NASS) Guideline of LSS and some other studies that there is insu cient evidence for a correlation between clinical symptoms or function and anatomic stenosis of the spinal canal on imaging [36][37][38] . Sangbong et al compared ODI and VAS before and 3 years after surgery in patients with different degrees of sttly enosis(without fracture), and they also did not nd a statistically signi cant difference in the prognosis of these patients 39 . But meanwhile ,we found that the prognosis of patients with preoperative lower extremity symptoms who choose decompression surgery is better than non-decompression surgery.…”
Section: Surgical Options and Prognosismentioning
confidence: 99%
“…However, the results in our study don't seem to support this tendency Table 7 .This is in line with the North American Spine Society (NASS) Guideline of LSS and some other studies that there is insu cient evidence for a correlation between clinical symptoms or function and anatomic stenosis of the spinal canal on imaging [36][37][38] . Sangbong et al compared ODI and VAS before and 3 years after surgery in patients with different degrees of sttly enosis(without fracture), and they also did not nd a statistically signi cant difference in the prognosis of these patients 39 . But meanwhile ,we found that the prognosis of patients with preoperative lower extremity symptoms who choose decompression surgery is better than non-decompression surgery.…”
Section: Surgical Options and Prognosismentioning
confidence: 99%